2013
DOI: 10.1158/0008-5472.can-12-4501
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Class of Anticancer Compounds Targets the Actin Cytoskeleton in Tumor Cells

Abstract: The actin cytoskeleton is a potentially vulnerable property of cancer cells, yet chemotherapeutic targeting attempts have been hampered by unacceptable toxicity. In this study, we have shown that it is possible to disrupt specific actin filament populations by targeting isoforms of tropomyosin, a core component of actin filaments, that are selectively upregulated in cancers. A novel class of anti-tropomyosin compounds has been developed that preferentially disrupts the actin cytoskeleton of tumor cells, impair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
169
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(173 citation statements)
references
References 55 publications
3
169
1
Order By: Relevance
“…1), was identified by an in silico small-molecule screening strategy for binding to a pocket in the C-terminus of Tpm3.1. We found that TR100 destabilized actin filaments containing Tpm3.1 both in cell culture models and also in pure actin filaments in vitro (12). Furthermore, we showed TR100 is cytotoxic for numerous cancer cell lines and induces a delayed growth pattern in several tumor models, including CHP134 human neuroblastoma xenografts.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…1), was identified by an in silico small-molecule screening strategy for binding to a pocket in the C-terminus of Tpm3.1. We found that TR100 destabilized actin filaments containing Tpm3.1 both in cell culture models and also in pure actin filaments in vitro (12). Furthermore, we showed TR100 is cytotoxic for numerous cancer cell lines and induces a delayed growth pattern in several tumor models, including CHP134 human neuroblastoma xenografts.…”
Section: Introductionmentioning
confidence: 74%
“…The tropomyosin isoform Tpm3.1 (previously known as Tm5NM1) is of particular interest as it is one of only two tropomyosins retained by essentially all tumor cells and is structurally divergent from the muscle tropomyosins (10,11). We previously reported a novel anticancer strategy based on disrupting actin filaments containing Tpm3.1 by targeting this tropomyosin isoform (12). The tool compound we used, TR100 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the changes of cytoskeletal components could provide novel therapeutic approaches to prevent cancer cell migration and metastasis (4). The targeting of cytoskeletal components, such as actin or tubulin (6,7), or regulatory proteins, such as Rho-ROCK or LIM kinases, has been shown to inhibit the invasive and metastatic behavior of cancer cells (8,9). However, the pharmacological inhibitors of cytoskeleton have not been very effective in clinical trials due to their nonspecific targeting of cytoskeleton in normal cells, which might cause side effects, such as cardiotoxicity (4,7,10).…”
mentioning
confidence: 99%
“…The targeting of cytoskeletal components, such as actin or tubulin (6,7), or regulatory proteins, such as Rho-ROCK or LIM kinases, has been shown to inhibit the invasive and metastatic behavior of cancer cells (8,9). However, the pharmacological inhibitors of cytoskeleton have not been very effective in clinical trials due to their nonspecific targeting of cytoskeleton in normal cells, which might cause side effects, such as cardiotoxicity (4,7,10). Moreover, in many cases, the anticancer drugs that target specific proteins might lose their efficacy after several months of treatment due to mutations of the proteins that result in the rise of drug resistance in cancer cells (11,12).…”
mentioning
confidence: 99%
“…Indeed, tropomyosin has been a favoured model for studying the mechanisms of exon splicing (Gooding et al 1994;Gooding and Smith 2008). The study of the function of tropomyosin outside of the muscle sarcomere has also become important (Lin et al 1985) especially in the context of altered actomyosin cell motility in cancer cells (Choi et al 2012;Franzén et al 1996;Helfman et al 2008;Stehn et al 2013), and extrapolation of these results suggests that the development of compounds directed against specific classes of malfunctional tropomyosins could also be possible in striated muscle.…”
mentioning
confidence: 99%